2006
DOI: 10.1111/j.1365-2699.2006.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic biogeography of the leafy liverwort Herbertus (Jungermanniales, Herbertaceae) based on nuclear and chloroplast DNA sequence data: correlation between genetic variation and geographical distribution

Abstract: Aim The cosmopolitan genus Herbertus is notorious for having a difficult taxonomy and for the fact that there is limited knowledge of species ranges and relationships. Topologies generated from variable molecular markers are used to discuss biogeographical patterns in Herbertus and to compare them with the geological history of continents and outcomes reported for other land plants.Location Africa, Asia, Azores, Europe, southern South America, northern South America, North America, New Zealand.Methods Phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 58 publications
(110 reference statements)
0
48
0
Order By: Relevance
“…A clear geographical structure was not observed in S. concreta, with the single African accession nested in one of the Neotropical subclades. The presence of African accessions in an otherwise exclusively Neotropical clade provides evidence for long range dispersal eastwards across the Atlantic, a scenario that has already been proposed for several clades of vascular plants (Renner, 2004) and liverworts (Heinrichs et al, 2005b;Feldberg et al, 2007). The geographical structure of some species clades and the restriction of some species ranges to single continents (Inoue, 1966;Grolle, 1972) indicate that successful long-distance dispersal is not a common phenomenon in Adelanthaceae.…”
Section: Biogeographymentioning
confidence: 88%
“…A clear geographical structure was not observed in S. concreta, with the single African accession nested in one of the Neotropical subclades. The presence of African accessions in an otherwise exclusively Neotropical clade provides evidence for long range dispersal eastwards across the Atlantic, a scenario that has already been proposed for several clades of vascular plants (Renner, 2004) and liverworts (Heinrichs et al, 2005b;Feldberg et al, 2007). The geographical structure of some species clades and the restriction of some species ranges to single continents (Inoue, 1966;Grolle, 1972) indicate that successful long-distance dispersal is not a common phenomenon in Adelanthaceae.…”
Section: Biogeographymentioning
confidence: 88%
“…More recent molecular studies have broadly supported these initial findings and added additional data (Juslén 2006b;Feldberg & Heinrichs 2006). In the broader study by Feldberg et al (2007), the small number of African specimens examined also showed limited variation, leading the authors to suggest that there may be only two species in Africa.…”
Section: Introductionmentioning
confidence: 65%
“…Grolle (1978) retained H. grossevittatus as a Mascarene endemic closely related to H. juniperoideus. More recent molecular work (Feldberg et al, 2007) has convincingly demonstrated the presence of H. juniperoideus in Africa. In the neotropics, H. juniperoideus is principally a Caribbean species.…”
Section: Species Descriptionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Long-distance dispersal events are often interpreted as the likely explanation for liverwort diversification (Heinrichs et al 2009) and wide disjunctions in distributional ranges can be attributed to long-distance dispersal (e.g. Shaw et al 2003, Heinrichs et al 2005, Feldberg et al 2007). Our results suggest that long-distance dispersal has played a role in shaping the distributional ranges of Acrobolbus species but we are unable to rule out the impact of vicariance.…”
Section: Discussionmentioning
confidence: 99%